Edifice complex the discourse of power in Marcos state architecture at the Cultural Center of the Philippines Complex - Lico, Gerard Rey A. (2000)
Architecture and urban design can never be "neutral". These practices are deeply ingrained within the structures of power, thereby making the act of designing spaces ideological. the very physicality of architecture makes claims on the maintenance of domain. Architecture as a system of representation is saturated with meanings and values. the linkage between power and architecture is the concept this thesis pursues. The power ingrained in architecture becomes more potent if it remains undetected. In this way hegemonic power camouflages itself to mask the internal conflict and struggles occuring in space, a kind of power that is "tolerable only on condition that it masks a substantial part of itself. Its success is proportional to its ability to hide its own mechanism." (Foucault 1980, 86) The presidency of Ferdinand Marcos (1965-1986) was a period of political unrest, transgression of human rights and great economic instability. Yet at the outset of his governance, it was predisposed to be a time of national rebirth and resurrection of old Filipino traditions. The First Lady, Imelda Marcos, packaged herself as a "Patroness of the Arts" and nurtured the so-called "cultural renaissance" under the aesthetic maxim: "the true, the good, and the beautiful." Locating the discursive axis of power and architecture along the grids of Philippine architectural history, the CCP Complex occupies a so far unexplored and unquestioned arena. The Cultral Center of the Philippines Comples, a 77-hectare reclaimed area, is an assembly of major Filipino modern architectural landmarks - The CCP Main Building, Folk Arts Theater, Philippine International Convention Center, PHILCITE, Philippine Plaza Hotel, Design Center, Manila Film Center, and Tahanang Filipino - that are identified with the Marcos regime. These structures serve as tangible manifestations of the regime's projection of power through architecture (often referred to as edifice complex), to signify the social re-engineering scheme under the New Society. The complex was utilized by the regime to consolidate the role of the Imelda Marcos as "Patroness of the Arts" and strengthen her position as Governor of Metropolitan Manila. The initial reclamation of 28 hectares from the sea in 1966 altered the physiology of the coastal urban landscape. Such urban intervention is in itself symbolic not only of the subversion of nature but of the regime's dictatorial power over the social, political, economic, cultural and ecological sphere of the period. It can be argued that the Marcos regime took this nexus architecture and society more seriously than any other administration in promoting the aesthetics of power in the built form. The regime's sonorous flirtation with monumental modern architectural imagery signified the modernizing thrust of a government, at the threshold of an envisioned rebirth through industrialization. An image that they sold to both the local and international market. Imelda Marcos even wrote monographs Architecture: the Social Art 91970) and Architecture for the Common Man (1975) to instill the seeds of this burgeoning role that architecture played in building the New Society. The monumental architecture in the CCP complex, underscored by the stark, rectangular, volumetric bouyancy of the Leandro Locsin (a modernist abstraction of the bahay kubo), by the indigenizing Neo Vernacular Tahanang Filipino of Francisco Manosa, and by the modernist reinterpretation of the Parthenon by Froilan Hong, were aesthetic devices for political legitimation. the complex became a venue in which mass civic rituals were conducted, with a theatrical quasi-fascistic trope, to forge an illusion of new a post-democratic collective, along the matrices of the New Society. To solicit consensus among the citizens, the Marcoses instinctively initiated architectural interventions, creating a scenographic backdrop to support a broad range of rituals of mass consolidation, and communal rites of passage. The Cultural Center of the Philippines Complex's seductive display was exploited to cast an illusion of the progressive urban landscape amid Third World urbanity. The complex and its architectural gems were built as representation of centralized power, evoking a sense of citizenship, a national memory of sacrifice that belongingness often demands. It confirms and consolidates the significance of cultural power - the power to impose a hegemonic vision for social domination in the guise of consensual image and national collectivity. Urban mythologies around the Cultural Center of the Philippines Complex were carefully consolidated and cogently dispensed by the regime through the capacity of architecture to solicit and inculcate among the citizenry the legitimacy of the regime. Over-scaling buildings in order to invoke ideas of greatness of civilization and to assure cultural inheritance to classical antiquity perpetuates a myth of monumentality. The use of this monumental scale in "Marcosian" architecture was "panoptical" in intent, impressing an aura of the dictator's omnipresence. The myth of modern progress involves the construction of favorable cosmopolitan architectural imagery. This was taken to its fullest concourse by the Marcos administration to encourage civic duty, tourism, and capital investment. the regime's massively loaned investments in buildings were meant to project internationally an impressive myth of "overnight industrialization" and render an illusion of fast-paced progress at work in the country. The myth of modernity implicates the use of an ahistorical modern architecture grammar. In building her monumental Romantic Nationalist architecture, Imelda instead of breaking away from the past, solicited her architects to self-consciously shore up allusions and iconography of the vernacular. The myth of collectivity and national identity posits the CCP Complex aspirations to express a collective yearning toward the wholeness of a nation. Through public monuments , a national memory is constructed, or invented, as the case may be. Its narrative was meant to inspire nationalism and self sacrifice for the common good. These myths are the consolidation of a unitary image of identity in architecture, hegemonically ordained by the regime in order to illuminate the promise of "national architecture" or an architecture for the nation.